Recombinant Human Thrombomodulin Has Additive Effects in Septic Patients Undergoing Continuous Hemodiafiltration Due to Intestinal Perforation. Issue 3 (September 2021) - Kono, Hiroshi; Hosomura, Naohiro; Amemiya, Hidetake; Kawaida, Hiromichi; Furuya, Shinji; Akaike, Hidenori; Kawaguchi, Yoshihiko; Sudo, Makoto; Ichikawa, Daisuke
ABSTRACT: Background: Disseminated intravascular coagulation (DIC) is associated with high mortality in patients with severe sepsis. The purpose of this study was to investigate the effects of recombinant human thrombomodulin (rhTM) in septic patients undergoing continuous hemodiafiltration (CHDF). Furthermore, effects of rhTM in acute lung injury, the first target organ in sepsis, were investigated using a sepsis model in rats. Methods: Clinical laboratory data, and the DIC, Sequential Organ Failure Assessment (SOFA), and Acute Physiologic and Chronic Health Evaluation (APACHE) II scores were compared between patients undergoing CHDF alone (rhTM− group; n = 23 cases) and patients undergoing CHDF treated with rhTM (rhTM+ group; n = 21 cases). Rats underwent cecal ligation and puncture (CLP) treated with or without rhTM, and acute lung injury (ALI) was analyzed. Production of TNF-α by isolated tissue macrophages (Mfs) was assessed. Results: The numbers of leukocytes, and C-reactive protein and D-dimer levels were significantly suppressed, and platelet counts recovered significantly faster in the rhTM+ group compared with the rhTM− group. The DIC score was reduced in both groups. The SOFA and APACHE II scores gradually reduced in the rhTM+ group. The CHDF treatment and ICU admission periods were shortened in the rhTM+ group compared with the rhTM− group. Treatment of rhTM was an independent factor for CHDF treatment period by multivariate analyses. CLP-induced ALI was significantly improved by rhTM. Increased TNF-α production by tissue Mfs was significantly suppressed by rhTM in vivo and in vitro Conclusion: Additive effects of rhTM treatment were observed in septic patients undergoing CHDF.